Fosravuconazole to treat severe onychomycosis in the elderly. Issue 2 (25th October 2020) - Noguchi, Hiromitsu; Matsumoto, Tadahiko; Kimura, Utako; Hiruma, Masataro; Kano, Rui; Kubo, Masahide; Fukushima, Satoshi; Ihn, Hironobu
Abstract: Fosravuconazole is a novel oral antifungal drug developed in Japan and used to treat tinea unguium since 2018. Its excellent oral absorbability and systemic bioavailability has enabled short‐duration therapy of 3 months. Furthermore, no concomitant drugs are contraindicated due to the presence of the mild inhibitor of cytochrome P450 enzyme which is responsible for polypharmacy adverse effects. Therefore, it can be safely administrated to elderly patients. Elderly patients (≥65 years old) with severe onychomycosis (≥50% nail involvement) were treated with oral fosravuconazole 100 mg once daily for 12 weeks. The rate of involvement improved from 86.6% to 28.1% ( P < 0.01). The efficacy (i.e. percentage of those rated as "improved" and better) and cure rate was 83.8% (31/37) and 29.7% (11/37), respectively. Furthermore, when focusing on the thin nail group (<3 mm), the efficacy and cure rate was 88.2% (15/17) and 58.8% (10/17), respectively. Although the serum γ‐glutamyltransferase levels increased in 21.6% (8/37), all patients recovered without any specific treatments.